TRUTH AND RECONCILIATION COMMISSION: AN ALTERNATIVE NON-JUDICIAL SETTLEMENT OF ALLEGATIONS OF GROSS HUMAN RIGHTS VIOLATIONS - Hendra A. Ginting; Marsetio Marsetio; Hafidz Abbas; Siswo Hadi Sumantri (Bajang Institute, 2022)
Difficulties and concerns over the inability of the formal legal process to deal with past humanitarian crimes, plus the concern that this road could lead the nation back to an authoritarian regime, is a strong impetus for the need for other mechanisms, or alternative solutions, which are then generally known as